Routine for Simulating Transmission Lines with Symmetrical and Asymmetrical Configurations Using a Real and Constant Modal Transformation Matrix - Caballero, Pablo Torrez [UNESP]; Kurokawa, Sergio [UNESP]; Kordi, Behzad; IEEE (Ieee, 2018)
Modal analysis is widely used in over-voltage and over-current studies of power systems. Modal transformation decouples a transmission line into its modes. Time-domain transmission line models usually require a real and constant modal transformation matrix. This paper proposes an approach that considers a real modal transformation matrix at a fix frequency to transform currents and voltages to the mode domain, and computes mode parameters using a frequency-dependent transformation matrix. Presented results demonstrate that the proposed approach is accurate and works with symmetrical, non-symmetrical and vertical transmission overhead line geometries.
Keywords: Transmission line modeling; electromagnetic transient analysis; multiconductor transmission lines